Poverty alleviation through CSR in the Indian construction industry. Issue 2 (2014) - ,; ,
Abstract : Purpose – Against the background of still insufficient achievements of particular millennium development goals (MDGs), contributions of private business to the alleviation of poverty have been increasingly called for. The purpose of this paper is to address this issue and explore the CSR strategies of transnational corporations (TNCs) regarding their impact on poverty alleviation within the construction industry in India, in order to gain an insight on how business is engaged in the improvement of the situation of the poor, and to derive recommendations on how pertinent CSR strategies can be further developed.Design/methodology/approach – The paper collects primary data for monitoring the CSR activities of the largest TNCs within the construction industry in India to conduct a CSR ranking of the sample TNCs in terms of CSR engagement with particular focus on poverty alleviation with respect to the MDGs.Findings – The findings show that the core business‐oriented focus of the CSR activities of the construction industry is mainly on MDG 1 and 7. Nevertheless, the construction industry still needs to gear its core business towards business models that enhance the housing conditions of the poor and to improve the general social conditions within this industry. Based on the findings the paper suggests a selected industry‐specific governmental CSR guidance to propel the implementation of CSR as business case.Practical implications – This work provides policy implications for the government and outlines the areas for business practitioners where CSR strategies should be enhanced to meet social needs and contribute to the alleviation of poverty.Originality/value – First of its kind study in scrutinizing the contribution of CSR to the alleviation of poverty, particularly regarding TNCs of the construction industry in India.